If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 2 = 3y Reorder the terms: 2 + 9x = 3y Solving 2 + 9x = 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 9x = -2 + 3y Combine like terms: 2 + -2 = 0 0 + 9x = -2 + 3y 9x = -2 + 3y Divide each side by '9'. x = -0.2222222222 + 0.3333333333y Simplifying x = -0.2222222222 + 0.3333333333y
| 3(X+4)=6x+2-3x+10 | | x+(-10)= | | 152=4x+3(7x-16) | | -5m-15+6m+2=15-8 | | 57-4x=-6x+65 | | (x+2)(x+3)=x*x-10 | | 8+4x=5y | | x-17=2x | | x^7+7x^6=0 | | 20x^2-17x-24= | | 2y-(-3-5y)=(y+2)+37 | | (8x+9)+(-6x-1)= | | -32x-4=44 | | 6-9p+11-2p+p-8+r= | | -11-5v=1-3v | | f(x)=9.5x-2 | | 2x+y=36.5 | | 3x+9=99 | | (-2+4)+(x-11)= | | 2w(-8w-3)= | | -2(-6n+7)+5n=-150 | | 12x-12y=4 | | 4.6x+56.4=12.9-9.9x | | 3+3x=15-3x | | 10+0.10x=.35x | | 90+15x=125+12x | | 45=x+0.13x+0.15x | | -5(4y+5)-11=-8(y+7)+4y | | 3k+5m-2mk+4+4mk-4k= | | 7+15x=3(5x+3) | | 5(2x+12)=18 | | 3.5=2.2 |